Efektivitas Dry Heat Treatment pada Benih dalam Menekan Gejala yang Diduga Disebabkan oleh Tobacco Mosaic Virus (TMV) pada Beberapa Galur Cabai (Capsicum annuum L.) Fase Vegetatif - Febri Kristianto; Sari Megawati; Suharno (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
Chili peppers (Capsicum annuum L.) are an important horticultural commodity susceptible to seed-borne virus infections, including Tobacco Mosaic Virus (TMV), which can reduce plant productivity. This study aimed to evaluate the effectiveness of Dry Heat Treatment (DHT) in suppressing the appearance of symptoms suspected to be related to TMV infection in several chili lines. The study used a factorial randomized block design (RBD) with two factors and four replications. The first factor consisted of seeds without DHT treatment and seeds with DHT treatment, while the second factor consisted of three chili lines. Observations were made on the percentage of plants showing symptoms of mosaic, chlorosis, leaf curl, and growth inhibition in the vegetative phase. Percentage data were transformed using arcsine transformation before being analyzed using analysis of variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that DHT treatment was able to reduce the percentage of symptomatic plants from 29.67% in untreated seeds to 10.33% in DHT-treated seeds. The combination of DHT-free treatment on the K3 strain resulted in the highest symptom percentage of 47.02%, while DHT treatment on all strains reduced the symptom percentage. The strain factor had no significant effect, while the interaction between DHT and the strain significantly affected the percentage of symptomatic plants. These results indicate that DHT has the potential to be applied as an environmentally friendly seed sanitation method to suppress seed-borne pathogens in chili plants. However, the identification of TMV in this study was based on field symptoms and has not been confirmed using serological or molecular methods.